The effect of back massage therapy for sleep quality in intensive care unit patients - Anggraheni, Astantika Afri; Kristinawati, Beti (Media Keperawatan Indonesia, 2023)
The quality of sleep of patients in the intensive care unit can be improved with massage therapy. One of the massage therapies that can be used to improve the quality of sleep patients is back massage therapy. The purpose of this review is to find out the effect of back massage therapy on the quality of sleep patients. Research methods use a Literature Review by looking for the latest and relevant sources. The database was obtained from PubMed, Google Scholar and Science Direct. A review was conducted on 3 articles that were relevant to the criteria namely by providing back massage therapy interventions and publications for the last 5 years (2016-2017). Back massage can improve sleep quality in critical patients with a duration of therapy of 10 minutes and 20 minutes. Measuring instruments used to assess the quality of a patient's sleep are the Verran Snyder-Halpern Sleep Scale (VSH Sleep Scale) and Wrist Actigraph. Back massage therapy is a nurse's self-contained action that can be done to improve the quality of sleep of critical patients in the Intensive Care Unit room.